PEDALANDO, PATINANDO E CAMINHANDO E VENCENDO O DIABETES: AÇÕES PARA O COMBATE A DOENÇAS DEGENERATIVAS - Noll, Gisele C.; Flora, Jessica P. D.; Baptista, Juliana B.; Jendrzyczkowski, Quele R.; Bertollo, Mauro; Göller, Dari F. (Salão do Conhecimento, 2013)
Resumo